Physiological skin changes during pregnancy - Ikram, Shanza; Malik, Aisha; Suhail, Majid (Journal of Pakistan Association of Dermatologists, 2018)
Objective To find out the frequency and pattern of physiological skin changes in pregnant women. Â Methods This descriptive study evaluated 200 consecutive pregnant females presenting to Dermatology Outpatient Department of Nawaz Social Security Hospital, Lahore over a period of one year. Â Results Total of twenty-three cutaneous manifestations were studied including striae gravidarum, hyperpigmentation, hair, nail and vascular changes. Majority of pregnant females complained of striae gravidarum (stretch marks) affecting 71.5% of study population closely followed by pigmentation i.e. linea nigra (64.5%) and melasma (63.5%). The most common vascular change noticed was palmar erythema (43.5%) and nail changes included leukonychia (15%), while diffuse hair loss (11.5%) was the most frequently found hair change. Â Conclusion The appreciation of common physiological skin changes during pregnancy will assist in better patient care during antenatal period. Â